Evaluation of the safety of hospitalized older adults as for the risk of falls - Sarges,Nathalia de Araújo (2017)
ABSTRACT Objective: To evaluate the safety of hospitalized older adults as for the risk of falls according to the parameters of the Morse Fall Scale. Method: Epidemiological, cross-sectional, prospective and descriptive study with n=75. Results: Average age of 71.3 years (SD±8.2); 58.7% male; 44% with low educational level; 38.7% hospitalized for cardiovascular diseases; average hospitalization of 10 days (SD±9.38); 78.7% with comorbidities; 61.3% with the calf circumference ≥ 31 cm; 62.7% were former smokers for more than 10 years; 65% did not drink alcohol; 100% did not have identification bracelet; 22.7% had similar names in the infirmary; 48% took up to five medicines; and 93.3% received some invasive procedure, especially the vessel puncture (65.3%). There was a high risk of falls in 52% of older adults. Conclusion: The results pointed to imminent risk of breach of patient safety, emphasizing the need for implementation of protocols and predictive scales such as the Morse scale.